Rice GLUTATHIONE PEROXIDASE1-mediated oxidation of bZIP68 positively regulates ABA-independent osmotic stress signaling - Zhou, Heng; Zhang, Feng; Zhai, Fengchao; Su, Ye; Zhou, Ying; Ge, Zhenglin; Tilak, Priyadarshini; Eirich, Jürgen; Finkemeier, Iris; Fu, Ling; Li, Zongmin; Yang, Jing; et al. (Molecular plant, 2022)
Osmotic stress caused by drought and high salinity is a significant environmental threat that limits plant growth and agricultural yield. Redox regulation plays an important role in plant stress responses, but the mechanisms by which plants perceive and transduce redox signals are still underexplored. Here, we report a critical function for the thiol peroxidase GPX1 in osmotic stress response in rice, where it serves as a redox sensor and transducer. GPX1 is quickly oxidized upon exposure to osmotic stress and forms an intramolecular disulfide bond, which is required for the activation of bZIP68, a VRE-like basic leucine zipper (bZIP) transcription factor involved in the ABA-independent osmotic stress response pathway. The disulfide exchange between GPX1 and bZIP68 induces homo-tetramerization of bZIP68 and thus positively regulates osmotic stress response by regulating osmotic-responsive gene expression. Furthermore, we discovered that the nuclear translocation of GPX1 is regulated by its acetylation under osmotic stress. Taken together, our findings not only uncover the redox regulation of the GPX1-bZIP68 module during osmotic stress but also highlight the coordination of protein acetylation and redox signaling in plant osmotic stress responses. This work elucidates the mechanisms of plants perceive and transduce redox signals in response to osmotic stress. We show that the rice thiol peroxidase GPX1 serves as a redox sensor and transducer in osmotic stress response.